Monitoring Kualitas Tanah pada Tanaman Cabai Rawit Menggunakan Sensor Soil Moisture dan Sensor pH Tanah Berbasis IoT - Ela Firliza; Imam Muslem; Heri Gustami (Jurnal Ilmu Komputer Aceh, 2026)
Chili peppers are one of the agricultural commodities that have a lot of commercial potential or high economic potential. Chili peppers require ideal soil pH and water content to produce maximum yields. Monitoring of agricultural land is generally done manually which can be time-consuming and labor-intensive. Therefore, a monitoring system is needed that can detect soil pH and water content in real time to increase the productivity and effectiveness of chili plants. This study developed an Internet of Things (IoT) based monitoring system. This system uses a soil moisture sensor to monitor soil moisture in chili plants and a soil pH sensor to monitor pH levels in the soil. This monitoring system was built using a soil moisture sensor and a pH sensor as input, an ESP32 DEV KT V1 microcontroller as a process and Telegram as an output. The system workflow is the sensor reads soil moisture and pH data, the data is sent to the ESP32 microcontroller for processing, from the Wi-Fi module the data is transferred to the server and the server sends the obtained data to the Telegram Bot to be displayed to the user